2017
DOI: 10.1155/2017/9428650
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Actinomycosis

Abstract: Introduction Actinomycosis is a chronic bacterial infection caused by Actinomyces, Gram-positive anaerobic bacteria. Its symptomatology imitates some malignant pelvic tumours, tuberculosis, or nocardiosis, causing abscesses and fistulas. Actinomycoses are opportunistic infections and require normal mucous barriers to be altered. No epidemiological studies have been conducted to determine prevalence or incidence of such infections. Objective To analyse the clinical cases of pelvic actinomycosis reported worldwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 46 publications
1
82
0
Order By: Relevance
“…Cases of pelvic actinomycosis with LNG-IUS use were not reported, but, in the majority of cases, the type of IUD used was not disclosed. 10 In this case report, the patient had a copper IUD in place for 6 years, which had been removed 4 months before presentation. Although the development of pelvic actinomycotic abscesses in women with IUDs is exceptionally rare, the diagnosis should be considered in women of reproductive age with a pelvic mass, especially in those with an IUD in place or recently removed.…”
Section: Discussionmentioning
confidence: 96%
“…Cases of pelvic actinomycosis with LNG-IUS use were not reported, but, in the majority of cases, the type of IUD used was not disclosed. 10 In this case report, the patient had a copper IUD in place for 6 years, which had been removed 4 months before presentation. Although the development of pelvic actinomycotic abscesses in women with IUDs is exceptionally rare, the diagnosis should be considered in women of reproductive age with a pelvic mass, especially in those with an IUD in place or recently removed.…”
Section: Discussionmentioning
confidence: 96%
“…Typical histological findings reveal the presence of necrosis with yellow sulfur granules of 1-2 mm in diameter, representing microcolonies of bacteria surrounded by lymphocytes, plasmocytes, histiocytes, and epithelium cells [15]. Bacterial confirmation is challenging and usually is accomplished in only 50% of cases, since culturing requires immediate specimen transport, prolonged anaerobic incubation and special equipment [25,26]. Identification of Actinomyces is possible using 16S rRNA gene sequencing [27].…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic actinomycosis is almost always associated with the use of an intrauterine contraceptive device (IUD) 2. In a systematic review by Alejandra García-García et al , 12 cases of pelvic actinomycosis were reported unrelated to IUD use3 and all patients had a prior pelvic procedure 2. We present an interesting case of pelvic actinomycosis which is not associated with a prior IUD use and a pelvic procedure.…”
Section: Introductionmentioning
confidence: 87%